Shaping resilient flood control system design through net present value assessments - Ghazi Al-Rawas; Mohammad Reza Nikoo; Mohammad Reza Hassani; Seyyed Farid Mousavi Janbehsarayi; Hossein Hosseinzadeh Kouhi; Mohammad Hossein Niksokhan (PLoS ONE, 2025)
Designing sustainable Flood Control Systems (FCSs) requires considering both the resiliency of the system and the long-term viability of investments. In this regard, our research aimed at integrating concepts of hydrological resiliency and cost-benefit analysis to design the most effective flood control network. To do so, first, the Storm Water Management Model (SWMM) was developed for simulating flood condition. Then, this model was coupled with the Pareto Envelope-based Selection Algorithm-II (PESA-II) to identify the optimal channels’ characteristics and generate a range of non-dominated solutions that balance implementation costs, system resilience (measured by the Simple Urban Flood Resilience Index, SUFRI), and overflow. Different flood management scenarios extracted for North Al-Batinah, Oman, a region under extreme flood events, exhibited high resilience and effectively reduced system overflow with reasonable costs. This highlights the value of optimization in resolving the conflicting objectives inherent in FCS design. Finally, net present values evaluated the long-term economic viability of each management scenario. The results revealed that strategies with moderate design costs and higher SUFRI values yielded optimal financial returns and substantial flood risk reductions. Also, the selected alternative based on net present value could reduce flood volume by 77.9%. This research underscores the critical role of incorporating resilience and cost-benefit analysis into FCS design to enhance the decision-making process.